Preparation of magnetic nano-composite-beads and their application to remediation of Cr(VI) and U(VI) from acid mine drainage - Tavengwa, Nikita Tawanda (My University, 2013)
Occurring parallel to the developments in imprinting technology are magnetic materials which are being applied increasingly in environmental remediation, medicine, biotechnology and many other fields. Combining the imprinting effects of the polymer and nano magnetic particles yields composite materials which are both selective to the template and magneto responsive for easy polymer removal from aqueous solutions. In this study, magnetic ion imprinted polymers with high recognition for uranyl ion (UO2 2+) in the presence of competing ions were synthesized by bulk and precipitation polymerizations. The uranyl template was removed from the magnetic polymer matric by 1M HCl and 1M NaHCO3 leachants to form cavities which were complimentary in shape and size to the template. Full characterization of the magnetite and magnetic polymers was achieved by use of the following characterization techniques: Raman spectroscopy (RS), Transmission electron microscopy (TEM), Energy dispersive spectrometry (EDS), Powder X-ray diffraction (PXRD) analysis, Brunauer, Emmett and Teller (BET) analysis, Ultraviolet visible (UV-vis) spectroscopy, Fourier-transform infrared (FTIR), Thermo-gravimetric analysis (TGA), Carbon, hydrogen, nitrogen and sulphur (CHNS) analysis, Diffuse reflectance spectroscopy (DRS) and Atomic force microscopy (AFM). Parameters which were optimized included sample pH, which gave an optimum value of 4. Magnetic IIP and NIP amounts which gave maximum adsorption capacities were found to be 50 mg for both of these adsorbents. The optimum contact time was found to be 45 minutes. The performance of all magnetic ion imprinted polymers (IIPs) was expectedly superior to that of the corresponding non imprinted polymers (NIPs) in all adsorption studies. The first rate constant (k1) and correlation coefficient (R2) values evaluated for the pseudo first order were found to be between 0.048-0.093 min-1 and 0.602-0.991 min-1, respectively. For the pseudo second order, second rate constant (k2) and correlation coefficient (R2) were found to be between 0.273- 0.678 and 0.9811-0.9992, respectively. The selectivity order observed was as follows: UO2 2+ > Fe3+ > Pb2+ > Ni2+ > Mg2+. The magnetic polymers selective to Cr(VI) were also synthesized and were leached with HCl to remove the template. The synthesized Cr(VI) magnetic polymers, the optimum pH obtained was 4 for both the magnetic IIP and the corresponding NIP. The amount of the adsorbent which gave the maximum adsorption was determined to be 20 and 65 mg for the magnetic IIP and NIP, respectively. A Cr(VI) concentration which was adsorbed maximally was from 5 mg L-1 which was therefore taken as the optimum. The maximum adsorption capacities for the magnetic polymers were 6.20 and 1.87 mg g-1 for the magnetic IIP and NIP, respectively. The optimum time for the adsorption of the Cr(VI) analyte was determined as 40 minutes. Investigation of the order of selectivity of anions followed the trend: Cr2O7 2- SO4 2- F- NO3- -.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science WITS University, Johannesburg, 2013
Keywords: Acid mine drainage.; Magnetic materials.; Uranium.; Chromium.